2008
DOI: 10.1111/j.1439-0531.2007.00927.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological Changes of the Feline Cervix, Endometrium and Placenta after Mid‐gestational Termination of Pregnancy with Aglepristone

Abstract: This study was conducted to investigate endometrial and placental structural changes that occurred in response to mid-gestational termination of pregnancy in queens using aglepristone, a progesterone receptor antagonist. Thirteen European Shorthair pregnant queens were either treated with aglepristone (10 mg/kg body weight; subcutaneously) twice on days 25 and 26 after first mating (am; group I; n = 9), or remained untreated and served as control (group II; n = 4). Queens of group I were ovariohysterectomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
10
0
2
Order By: Relevance
“…On the contrary, ALI was effective at inducing abortion in queens at days 21–22 of pregnancy. Whereas previous reports have shown that ALI was effective in the queen to terminate pregnancy on days 25–26 without side effects (Georgiev and Wehrend , ), to our knowledge, this is the first study to report the lack of efficacy of CLO to induce abortion in the queen. Previous studies using of PGF in cat at 21–25 days of a pseudopregnancy depressed luteal function, but did not induce complete luteolysis (Shille and Stabenfeldt ).…”
Section: Discussionmentioning
confidence: 52%
“…On the contrary, ALI was effective at inducing abortion in queens at days 21–22 of pregnancy. Whereas previous reports have shown that ALI was effective in the queen to terminate pregnancy on days 25–26 without side effects (Georgiev and Wehrend , ), to our knowledge, this is the first study to report the lack of efficacy of CLO to induce abortion in the queen. Previous studies using of PGF in cat at 21–25 days of a pseudopregnancy depressed luteal function, but did not induce complete luteolysis (Shille and Stabenfeldt ).…”
Section: Discussionmentioning
confidence: 52%
“…2 is also known from literature (Berman 1974;Johnston et al 2001a). Besides Georgiev et al (2008) histologically observed bleedings at the paraplacenta and the placental girdle, within the uterine lumen and the interstitial mucosal stroma of the cervix following induction of abortion with aglepristone on days 25 ⁄ 26.…”
Section: Discussionmentioning
confidence: 97%
“…Another alternative to induce abortion is the use of antiprogestins, such as aglepristone (ALI). Treatment with ALI has been proven to be safe and effective for early, middle, and late pregnancy termination in the queen [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%